Deklarasi Anies - Muhaimin dan Konflik Ideologi NU Versus PKS di Pentas Politik Nasional - Dalle, Muhammad (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
The conflict between NU and PKS is an ideological battle rooted in political competition, notably surrounding the 2024 presidential election. Escalating tensions involve Nasdem's support for Anies Baswedan and PKS's selection of Muhaimin Iskandar as vice-presidential candidate. NU figures derisively depict the Anies-Muhaimin pair, backed by PKS, as Wahhabi groups associated with the Muslim Brotherhood. Utilizing power cube theory and Gramsci's hegemony, this research analyzes the conflict, revealing internal disputes within PKB across various power layers. The conflict extends nationally and internationally, involving key figures and transnational issues. However, attacks on the Anies-Muhaimin coalition rely on outdated narratives. NU's actions, stemming from Gus Dur's legacy, are influenced by political factors and personal interests. Hidden conflicts between NU and Muhammadiyah are also pivotal. The author suggests NU cadre unity, resolving longstanding conflicts, and Islamic party unity to confront perceived nepotism, secularism, and oligarchic favoritism in the regime.